The Fight Over Food Producers, Consumers, and Activists Challenge the Global Food System - Bonanno, Alessandro 1954-; Constance, Douglas H.; Friedland, William; Guptill, Amy; Johnston, Josée; Jussaume, Raymond; Kondoh, Kazumi; Long, Norman; Middendorf, Gerad; Middendorf, Gerad; Munro, William; Ransom, Elizabeth; et al. (Penn State University Press, 2021)
"One problem with the food system is that price is the bottom line rather than having the bottom line be land stewardship, an appreciation for the environmental and social value of small-scale family farms, or for organically grown produce." -Interview with farmer in Skagit County, WashingtonFor much of the later twentieth century, food has been abundant and convenient for most residents of advanced industrial societies. The luxury of taking the safety and dependability of food for granted pushed it to the back burner in the consciousness of many. Increasingly, however, this once taken-for-granted food system is coming under question on issues such as the humane treatment of animals, genetically engineered foods, and social and environmental justice. Many consumers are no longer content with buying into the mainstream, commodity-driven food market on which they once depended.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mai 2021)
Keywords: SOCIAL SCIENCE / Sociology / Rural; Agriculture -- Social aspects; Food supply -- Social aspects